Diffraction contrast tomography of polycrystalline alumina - Marrow, T; King, A; Reischig, P; Rolland Du Roscoat, S; Ludwig, W (2009)
Diffraction Contrast Tomography has been used to map the three-dimensional microstructure of a ceramic (coarse grain size polycrystalline alumina) for the first time. This new synchrotron technique determines, non-destructively, the crystallographic orientation of each grain from its diffraction geometry. The 3D grain shapes are also obtained from projected images of the grains in the diffraction condition. Grain boundary structure can therefore be characterised in terms of the physical grain boundary plane orientation and the crystal misorientation of the adjacent grains.